2021
DOI: 10.1140/epjc/s10052-021-09560-4
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and stability of traversable wormhole solutions in modified theories of gravity

Abstract: We study Morris–Thorne static traversable wormhole solutions in different modified theories of gravity. We focus our study on the quadratic gravity $$f({\mathscr {R}}) = {\mathscr {R}}+a{\mathscr {R}}^2$$ f ( R ) = R + a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Now, we think that it will be appropriate to compare our results for ZTF Casimir wormhole with the usual Morris-Thorne wormholes within the same f (R) theories of gravity considered. Morris-Thorne wormholes were investigated in details within the both quadratic and power-law gravities in the work [42]. In the quadratic gravity, it was shown that NEC, SEC for radial and tangential pressures were respected only for α ≥ 0 and only in the case, when α is relatively small (which coincides well with the Casimir wormholes, that was investigated in the present study).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Now, we think that it will be appropriate to compare our results for ZTF Casimir wormhole with the usual Morris-Thorne wormholes within the same f (R) theories of gravity considered. Morris-Thorne wormholes were investigated in details within the both quadratic and power-law gravities in the work [42]. In the quadratic gravity, it was shown that NEC, SEC for radial and tangential pressures were respected only for α ≥ 0 and only in the case, when α is relatively small (which coincides well with the Casimir wormholes, that was investigated in the present study).…”
Section: Discussionsupporting
confidence: 64%
“…Casimir Energy is currently the only possible substitute for exotic matter, that could be obtained in the laboratory. Firstly, we could present energy conditions, that we will use in this paper [42]:…”
Section: A Energy Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of compact objects, such as stellar structures, can be also examined through the Tolman-Oppenheimer-Volkov (TOV) equation, initially introduced in the context of neutron stars [39,40]. Hence, the stability conditions for wormholes could be investigated by employing an equilibrium condition obtained from the TOV equation [41][42][43][44]. Combining the Morris-Thorne metric ansatz (2.2) with the conservation law of stress-energy tensor ∇ µ T µν = 0, we obtain the following TOV equation in a 2 + 1 dimensional spacetime:…”
Section: Stability From Tov Equationmentioning
confidence: 99%
“…Here, a specific logarithmic corrected f (Q) type function is considered, which is defined as [30,31]…”
Section: The Logarithmic Corrected F (Q) Gravity Modelmentioning
confidence: 99%